Study of the Influence of a Solvent on the Crystal Structure of an Ethyl-Substituted Bisthiosemicarbazone Ligand - Sandra Fernández-Fariña; Uxía Barreiro-Sisto; Isabel Velo-Heleno; Ana M. González-Noya (Chemistry Proceedings)
A potentially dianionic symmetric bisthiosemicarbazone ligand H2LEt has been prepared by a condensation reaction between two equivalents of 4-N-ethyl-3-thiosemicarbazide and one equivalent of 4,4′-methylenebis(acetophenone). The crystal structures obtained from solvents with different donor abilities were studied. The recrystallization of H2LEt from methanol and dimethylsulfoxide enables the isolation of single crystals suitable for the X-ray diffraction studies of [H2LEt] 1 and [H2LEt]·CH3SOCH32, respectively. This study shows that the solvent does not affect the macrostructure but influences the microstructure of the ethyl-substituted bisthiosemicarbazone ligand H2LEt.